Pharmacokinetics, Pharmacodynamics and Dermal Distribution of 5-Methoxypsoralen Based on a Physiologically Based Pharmacokinetic Model to Support Phytotherapy Using Brosimum gaudichaudii - Martins, Frederico Severino; Sy, Sherwin K.B.; Fonseca, Maria José Vieira; de Freitas, Osvaldo (Planta Medica, 2020)
The treatment of vitiligo includes the combination of psoralens and ultraviolet type A exposure. Psoralens belong to a group of natural furanocoumarins that cause the skin to become sensitive temporarily to ultraviolet type A. The aim of this study was to develop a physiologically based pharmacokinetic model of 5-MOP from Brosimum gaudichaudii to support psoralen and ultraviolet type A therapy. A study of rats was used to establish and validate rat tissue distribution. The same chemical-specific parameters used in the rat model were also employed in the human model to project human pharmacokinetics. The highest exposures in the rats were in the brain and skin. Following a single dose of 1.2 mg/kg 5-MOP in humans, the model predicted a maximum concentration of 20 ng/mL and an area under the curve of 125 ng.h/mL, matching clinical results. The half-maximum melanogenesis concentrations in B16F10 cells were 29.5, 18.5, 11.5, and 6.5 ng/mL for synthetic 5-MOP, synthetic 5-MOP with ultraviolet type A, B. gaudichaudii alone, and B. gaudichaudii plus ultraviolet type A, respectively. Physiologically based pharmacokinetic model prediction in humans supported a once-every-two-day regimen for optimal melanin production. This type of framework can be applied to support strategies for dose selection and to investigate the impact of drugs on melanocyte recovery.
Keywords: vitiligo; skin; psoralen; PUVA; Brosimum gaudichaudii; Moraceae